The quest for reality : subjectivism and the metaphysics of colour - Stroud, Barry (Oxford University Press, 2000)
Barry Stroud investigates the way humans perceive colour in the world around them in this model of subtle, elegant and rigorous philosophical writing. The central question he asks is whether colour is real or a subjective experience.